2021
DOI: 10.1088/1361-665x/abe4e5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal commutative dynamics in semi-crystalline polymers undergoing multiple shape memory behavior

Abstract: Semi-crystalline polymers offer great opportunities for design and tuning of multi-shape memory effect (multi-SME) through their programmable melting transitions. However, coexistence of amorphous and crystalline components as well as their multiple interfaces results in complex cooperative dynamics. In this study, we propose a one-dimensional multi-modal dynamic model to describe the commutative and cooperative dynamics in semi-crystalline shape memory polymers undergoing multi-SME. A three-phase model and Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Since the PET is semi-crystalline or amorphous based on the curing condition, the molecules are rigid, with no free volume to stretch. Thus, the PET core sandwich panels produced lesser load absorption, whereas, in PVC, the load could transfer uniformly without crack propagation and cleavage formation [66]. However, the PVC core unit contains composites that offer higher flexural strength.…”
Section: Sandwich Composite Three-point Bendingmentioning
confidence: 99%
“…Since the PET is semi-crystalline or amorphous based on the curing condition, the molecules are rigid, with no free volume to stretch. Thus, the PET core sandwich panels produced lesser load absorption, whereas, in PVC, the load could transfer uniformly without crack propagation and cleavage formation [66]. However, the PVC core unit contains composites that offer higher flexural strength.…”
Section: Sandwich Composite Three-point Bendingmentioning
confidence: 99%
“…They can sustain large deformation and show responsiveness to multiple stimuli [2,3] . Due to the broad potential applications in biomedical and aerospace areas, SMPs have received considerable attention in the past two decades [4][5][6][7][8][9][10] . The shape-memory effect has been reported and optimized in various polymeric systems to improve the performances of shape fixity and shape recovery [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on an extensive literature, we found that the combination of crystal phases and CANs has resulted in significant improvements in the mechanical performance of the semicrystalline thermoset epoxy [30]. However, the self-healing and toughening mechanisms behind these phenomena have not been fully understood, and both theoretical models and experimental studies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%